2019
DOI: 10.4103/ortho.ijortho_207_19
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Evaluation of Modified Uninstrumented Open-door Cervical Laminoplasty for Ossified Posterior Longitudinal Ligament with Cervical Myelopathy

Abstract: Study Design: This was a retrospective study. Purpose: To evaluate the short term outcomes of a novel self-developed technique of performing uninstrumented open-door cervical laminoplasty (ODCL) in patients with cervical myelopathy secondary to ossified posterior longitudinal ligament (OPLL). Review of Literature: Published literature on cervical laminoplasties largely focuses on the outcomes of instrumented variants. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We use an uninstrumented variant developed by us to keep the gap open and provide support for the hinge to heal. A non-absorbable polyester suture material such as Ethibond (© Johnson & Johnson Medical N.V., Belgium) is used to keep the laminar flaps elevated [10]. The wound is closed over layers and a drain is kept.…”
Section: Posterior Cervical Laminoplastymentioning
confidence: 99%
“…We use an uninstrumented variant developed by us to keep the gap open and provide support for the hinge to heal. A non-absorbable polyester suture material such as Ethibond (© Johnson & Johnson Medical N.V., Belgium) is used to keep the laminar flaps elevated [10]. The wound is closed over layers and a drain is kept.…”
Section: Posterior Cervical Laminoplastymentioning
confidence: 99%
“…Dhillon et al also observed that the JOA score signi cantly increased after UODL in patients with cervical OPLL (from 9.2 ± 1.1 13.7 ± 0.9)(17). Cha et al reported (18) that in patients with multilevel cervical myelopathy, the JOA score roses from 9.4 ± 3.3 preoperatively to 13.8 ± 2.2 after one year following UODL.…”
mentioning
confidence: 92%